Strategy of Managing Disagreements and Resolving the Issue of Takfeer-e-Muslim - Maryam Rathor; Dr. Shahzadi Pakeeza; Fariha Fatima (Al-Qanṭara, 2024)
In Islam, religious or cultural diversity is considered as a sign of Allāh (عزوجل) and it contains several injunctions with the aim to establish peace for social behavior, managing disputes and resolving the disagreements. It is the religion of unity and pacific which addresses the mankind to live together and collaborate with each other even during disagreements on religious matters and on differences of culture and civilization. The article examines the rules of making takfeer on the person to highlight the sensitivity of the concept of takfeer and later outlines the Islamic ethical values with the aim to make various sects of Muslims in Pakistan live peacefully not only with themselves but with the people having disagreement and difference of opinions as well. Keywords: Peace and harmony, Ethics, Consultation, Justice, Apostacy, Disbeliever, Disagreements, Charter of peace, Etiquettes, Behavioural factors.